Determinants of Retail Patronage - A Systematic Literature Review Perspective (Global Business Management Review (GBMR), 2022)
This paper aims to study the determinants of retail patronage to shopping centres. Previous studies have indicated that the long term success and profitability for any shopping centre in these challenging economic times depends on the level of retail patronage. This paper defines retail patronage as store choices and frequency of visits (loyalty). The dimensions used to measure includes product related factors (product features i.e. product quality and price), market related factors (services provided by retailers / shopping centre management) and personal factors (which pertains to the demographics of the consumers). For this study, previous empirical studies are synthesized in order to perform a critical review of the literature. The method used to synthesize this study includes the studying of the total effects of the different dimensions. Whilst the findings have indicated that retail attributes or shopping environments remain crucial to shoppers, shopping centre management should also pay attention to the market related factors such as providing convenience, improvement of quality aspects etc. Further findings from this study conclude that more studies should incorporate customer emotions as well as customer characteristics in order to establish their intentions to patronage intentions.